Focal and perifocal changes in tissue energy state during middle cerebral artery occlusion in normo- and hyperglycemic rats - Folbergrová, J; Memezawa, H; Smith, M L; Siesjö, B K (Journal of cerebral blood flow and metabolism, 1992)
The objective of the present study was to assess changes in cellular energy metabolism in focal and perifocal areas of a stroke lesion and to explore how these changes are modulated by preischemic hyperglycemia. A model for reversible occlusion of the middle cerebral artery (MCA) in rats was used to study changes in energy metabolism. Following MCA occlusion for 5, 15, or 30 min in normoglycemic rats, the tissue was frozen in situ, and samples from the lateral caudoputamen and from two neocortical areas were collected for metabolite analyses, together with a control sample from the contralateral, nonischemic hemisphere. Two other groups, subjected to 30 min of MCA occlusion, were made hyperglycemic by acute glucose infusion or by prior injection of streptozotocin. Enzymatic techniques were used for measurements of phosphocreatine, creatine, ATP, ADP, AMP, glycogen, glucose, pyruvate, and lactate. The neocortex of the contralateral, nonischemic hemisphere had labile metabolites that were similar to those measured in control animals. Ipsilateral neocortex bordering the focus, and thus constituting the "penumbra," showed mild to moderate ischemic changes. In the "focus" (lateral caudoputamen plus the overlying neocortex), deterioration of energy state was rapid and relatively extensive (ATP content 20-40% of control). After 5 min of occlusion, no further deterioration of metabolic parameters was observed. Substrate levels were markedly reduced, and lactate content rose to approximately 10 mM kg-1.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Diabetes Mellitus, Experimental; adeninnukleotidy; experimentální diabetes mellitus; Hyperglycemia; Male; Rats; Blood Pressure; Brain; inbrední kmeny potkanů; hyperglykemie; laktáty; Animals; kyselina mléčná; zvířata; Arterial Occlusive Diseases; mužské pohlaví; mozek; Rats, Inbred Strains; krevní tlak; glukosa; Body Temperature; krysa rodu Rattus; arteriální okluzní nemoci; tělesná teplota; energetický metabolismus; Adenine Nucleotides; Lactates; Energy Metabolism; Lactic Acid; Glucose